Strategija razvoja slovenskega javnega elektronskega arhiva "e-ARH.si" - Hajtnik, Tatjana (Knjižnica, 2011)
The Slovenian National Archive and six regional archives (Slovenian Archival Public Service, SAPS) have to provide for archival material created by public administration and representing an important part of the Slovenian cultural heritage. In addition, it provides legal security for the state its institutions and individuals. As a result of the increasingly intensive e-business in public administration a growing amount of archival material i the digital form is generated which should be safely preserved and archived for the long term. The Republic of Slovenia has to establish a suitable environment - the Slovenian Public Electronic Archive. It represents a complex environment, designed for the digital preservation. It includes procedures to ingest archival material in a digital form into the relevant Archives, professional treatment, long-term preservation in accordance with regulations and it provides effective management and use of this material. The first step is a clearly defined strategy of development of the Slovenian Public Electronic Archive. The strategy was prepared by SAPS on the basis of different professional backgrounds. The most significant are: e.g. the long-term implementation of e-governance ARH.si. which is directly under the supervision of SAPS, cooperation with other state institutions, legal requirements, standards and best practices, the availability of electronic archives, digitization of the archival material in a physical form. The paper presents the main highlights of the strategy and its implementation plan. The strategy is closely connected to other solutions in the e-commerce and consequently also to the retention of e-documents and e-archives of the public administration which is in fact also the most important creator of archival materials.
Keywords: arhivi; arhivsko gradivo; elektronski arhivi; upravljanje z dokumenti